Investigational approach to adenoviral conjunctivitis: comparison of three diagnostic tests using a Bayesian latent class model - Sundaramurthy, Raja; Dhodapkar, Rahul; Kaliaperumal, Subashini; Harish, Belgode Narasimha (The Journal of Infection in Developing Countries, 2018)
Introduction: Highly contagious adenoviral conjunctivitis represents 15-70% of all conjunctivitis worldwide. Human adenovirus (hAdV) serotypes 3,4,7,8,19 and 37 contributes to 89% of all adenoviral conjunctivitis. Accurate and rapid diagnosis of adenoviral infections at serotype level could prevent misdiagnosis, spread of disease, unnecessary antibiotic use and increased treatment costs. Methodology: Sixty-two suspected viral conjunctivitis cases were recruited from November2013-January2015. Swabs collected from inferior palpebral conjunctiva and processed for viral culture (Hep2 cell line), immunofluorescence assay (IFA) and polymerase chain reaction (PCR) (targeting hexon gene). Serotype 3,4,7,8,19 and 37 identification was carried out with an optimized multiplex-PCR (based on hypervariable region of hexon gene) and confirmed by sequence analysis. Bayesian Latent Class Model (LCM) analysis was used to compare sensitivity and specificity of three tests. Results: Adenovirus was detected in 54.8% (34/62) of cases by combination of all three methods. Culture was positive in 23/34 cases (67.6%). PCR and IFA detected adenovirus in 24 (70.5%) and 21 (61.7%) cases respectively. LCM analysis revealed, sensitivity and specificity of PCR, Culture and IFA was 77.8% and 92.4%; 72.2% and 90.8%; 67.6% and 92.9% respectively. Serotyping by multiplex-PCR showed, two cases each were hAdV3 and hAdV4, 18 hAdV8 and two remained unidentified. Results of Multiplex-PCR and sequence analysis showed 100% concordance Conclusion: LCM analysis revealed, PCR is the most appropriate method for identification. Multiplex-PCR is a simple and rapid method (serotypes identification within two days); owing its short turnaround time and accuracy, it can be used as a diagnostic tool for surveillance of adenoviral keratoconjunctivitis.